Religious Education, Smoking Laws and Islamic Organisations with Mosque Worshipers Smoking Behaviour - Watni Marpaung (Universitas Islam Negeri Sumatera Utara, Medan, 2022)
There are differences in fatwas about smoking by Islamic organizations, which will impact worshipers' smoking behavior. Behaviors like smoking will be linked to internal factors like being part of an Islamic group, getting religious education, and knowing about the smoking law. Smoking is an activity carried out by many people in Indonesia. Even though smoking is dangerous to health, it is triggering non-communicable diseases, which cause an increase in disability and death. This study follows a cross-sectional design by interviewing 530 Muslims who have prayed in the mosque for the last 14 days. This study used a pre-prepared closed questionnaire. Frequency distribution and cross-tabulation were carried out using JAPS 16 software. The results of this study show that people with religious education are less likely to smoke (12.1% at boarding schools and 36.7% at madrasah aliyah). Mosque worshipers who think smoking has a haram law tend never to smoke (34.1%), while among those who view smoking as a makruh law, many still smoke (4%). The results of this study indicate that Muhammadiyah organizations tend never to smoke (5.8%), Salafi organizations tend not to smoke (1.7%), and Nahdatul Ulama organizations tend not to smoke (80.8%). Many members of the Nahdatul Ulama organization still smoke cigarettes (5.5%). There is a strong link between smoking and things that happen on the inside, like religious education, smoking laws, and Islamic groups. Islamic organizations and smoking laws are factors that have an impact on the smoking behavior of mosque congregations.